Systemic lupus erythematosus and primary cerebral lymphoma. Issue 741 (July 1987) - Woolf, A. S.; Conway, G.
Abstract : A woman with a 21 year old history of systemic lupus erythematosus (SLE) is presented. During a period of low connective tissue disease activity she developed sudden difficulty in walking and after much investigation was found to have a primary lymphoma of the brain. She died 6 months after this diagnosis from meningeal spread, despite radiotherapy to the tumour. The association between SLE and lymphoma is discussed.